Acupoint Catgut Embedding Alleviates Neuropathic Pain by Regulating Sigma-1 Receptor Expression - Xie, Heng-tao; Feng, Xiao-bo; Du, Kai-rong (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: apoptosis